Early warning systems in maternity care: A qualitative evidence synthesis of maternity care providers' views and experiences. (September 2022) - Smith, Valerie; O'Malley, Deirdre; Cithambaram, Kumaresan
Highlights: Maternity early warning systems (MEWS) were viewed as an aid to clinical care. Maternity care providers hold contrasting views as to the impact of MEWS on workload. Inadequate training in MEWS use was viewed as affecting compliance with MEWS The findings will help managers optimise MEWS implementation in clinical settings. Abstract: Objective: To gain insight and understanding, from the perspective of maternity care providers, on the use and application of maternity early warning systems (MEWS) in clinical practice. Design: A qualitative evidence synthesis was conducted. MEDLINE, CINHAL, Web of Science Core Collection and Maternity and Infant Care (MIDIRS), from inception to March 2021, were searched for eligible studies. Grey literature sources were also searched for unpublished studies. The methodological quality of included studies was assessed by at least two reviewers using an Evidence for Policy and Practice Information and Co-ordinating (EPPI) Centre quality assessment tool. Thomas and Harden's thematic synthesis approach was used to guide the data synthesis. Confidence in the findings was assessed using the Grading of Recommendations Assessment, Development and Evaluation of Confidence in the Evidence from Reviews of Qualitative research (GRADE-CERQual). Setting and Participants: Included studies reported on maternity care providers involved in caring for pregnant or postpartum women in any birth setting. Studies were mostly qualitative in design, although survey designs with open-ended questions that provided qualitative data were eligible for inclusion if the qualitative data had been subjected to formal analyses. Findings: Eight eligible studies, reported across nine records, were identified in the search and included in the review. Three themes representative of maternity care providers' views and experiences of MEWS were generated from the synthesis. These were ' Aid to clinical care provision', ' Impact on workload' and ' Factors affecting MEWS implementation' . MEWS was viewed as a useful tool in guiding clinical care, and for identifying deterioration and the need to escalate care. Some maternity care providers viewed MEWS as beneficial in easing workload burden. Others, however, viewed MEWS as adding to workload because of repetition and duplication. Training in MEWS was considered inadequate and concern existed for some care providers that MEWS would lead to deskilling or eroding of professional judgement. Key conclusions and implications for practice: Maternity care providers hold diverse views on the use of MEWS in clinical practice. While almost all consider MEWS a helpful aid for guiding clinical care, barriers to implementation were identified. These included added workload burden, inadequate training, and concern for deskilling. Attending to implementation barriers will help optimise use of MEWS in clinical practice as currently recommended.